Analisis Kualitatif Revitalisasi dan Strategi Budidaya Kopi Berkelanjutan di Halmahera Timur: Studi Kasus Koperasi Tani Permata Buli, Desa Geltoli, Kecamatan Maba - Deiby Elsa Gisisi; Nining Purwaningsih (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
The revitalization of coffee plantations is a strategic effort to enhance productivity and quality, particularly in Halmahera, which has favorable agroclimatic conditions. This study aims to analyze the implementation of revitalization programs and coffee cultivation practices adopted by the Permata Buli Farmers’ Cooperative in Geltoli Village, Maba District. A qualitative approach was used, involving field observations, interviews with farmers, and secondary data analysis related to coffee production and marketing. The results indicate that the adoption of sustainable farming techniques, such as selecting high-quality seedlings, agroforestry systems, and proper post-harvest management, contributes to increased productivity and coffee quality. Additionally, cooperative institutional support, access to capital, and government policies play significant roles in the success of coffee plantation revitalization. This study recommends optimizing farmer training, improving market access, and strengthening partnerships with the coffee processing industry to create a more sustainable and competitive coffee farming system.